Title History, present condition and indicator of forestry in Higashiyoshino - TAKAHASHI, Erina; TAKEUCHI, Michiyuki (Forest research, Kyoto, 2024)
Higashiyoshino is a center of Yoshino forestry. The feature of Yoshino forestry is said to be dense planting, frequent thinning, and long-term forest management. These techniques have been established over a long time. In Higashiyoshino, the sugi and hinoki forests aged 41-50 years and 71 years and older each occupy about 20% of the plantation area, and the old stands are increasing. In recent years, the stumpage price and the log price are sluggish, and in Higashiyoshino, the decreasing population and aging of the workers, are becoming serious problems. Thus, due to the shortage of labor, some of the techniques of long-term forest management are on the verge of disappearance. Recently, although there is a tendency to continue thinning and avoid clear cutting in the Yoshino area, the aging stands inevitably remain in Higashiyoshino under the above circumstances. Yet, some stands around the age of 100 years old are now declining, and forest management must be reconsidered. It is necessary to organize the techniques for further long-term forest management in Higashiyoshino.